2019
DOI: 10.1103/physrevlett.123.190602
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Entanglement Spectra under Generic Quantum Dynamics

Abstract: We characterize the early stages of the approach to equilibrium in isolated quantum systems through the evolution of the entanglement spectrum. We find that the entanglement spectrum of a subsystem evolves with at least three distinct timescales. First, on an o(1) timescale, independent of system or subsystem size and the details of the dynamics, the entanglement spectrum develops nearest-neighbor level repulsion. The second timescale sets in when the light-cone has traversed the subsystem. Between these two t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…While we do not have an analytical proof of the above scalings, we present a physical picture that elucidates the evolution of the ES in the second stage in terms of the operator spreading of the inserted T gates, as depicted in Fig. 1 (right panel) [15,16]. We show that each T gate spreads over a spatial region that grows linearly in time, and hence the operator spreading of T gates should determine the timescale for the saturation to Wigner-Dyson distribution of the wavefunction ES.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…While we do not have an analytical proof of the above scalings, we present a physical picture that elucidates the evolution of the ES in the second stage in terms of the operator spreading of the inserted T gates, as depicted in Fig. 1 (right panel) [15,16]. We show that each T gate spreads over a spatial region that grows linearly in time, and hence the operator spreading of T gates should determine the timescale for the saturation to Wigner-Dyson distribution of the wavefunction ES.…”
Section: Introductionmentioning
confidence: 91%
“…It has been shown that the dynamics of ES is able to distinguish between random unitary circuits of different complexities [7][8][9], as well as thermalization and localization phases of the underlying Hamiltonian [10][11][12][13]. Moreover, the onset of level repulsion in the ES signals the spreading of operator fronts, which serves as an important diagnostic of quantum chaos and information scrambling [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we will study the spectral form factor of the entanglement Hamiltonian. While it is also meaningful to study the spectral correlations of the RDM of the subsystem [23,37], it is easier to consider the entanglement Hamiltonian directly due to its intimate relationship with the RDM, see Eq. (7).…”
Section: Entanglement Hamiltonian and Correlation Matrixmentioning
confidence: 99%
“…It has been seen recently that the dynamics of the spectral form factor serves as a useful probe in understanding the various stages of approach to thermalization in chaotic (nonintegrable) models [37] through the study of the correlations in the spectrum of the entanglement Hamiltonian. It has been noticed that there is a certain correspondence between the dynamics of the level repulsion, entanglement entropy [38][39][40], and the development of the spectral form factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation